An Analysis Of Reading Comprehension Question Level On ″Talk Active ″ English Textbook - Yeri; Ivan Achmad Nurcholis; Yupika Maryansyah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to evaluate the levels of reading comprehension questions found in the Talk Active English textbook for tenth graders. The research employed a descriptive approach and utilized Clymer’s taxonomy, as cited by Brassel (2008:17–18), which categorizes reading comprehension into three levels: literal, inferential, and critical. These categories were organized into a checklist table for analysis. Results indicated that out of ten units in the textbook, seven contained questions from each level, totaling 80 questions overall. Specifically, the distribution included 56 literal comprehension questions, 14 inferential questions, and 10 critical comprehension questions. The study suggests that teachers should evaluate students’ reading abilities when choosing textbooks to ensure that the material is suitable for their grade level and learning needs. Keywords: reading comprehension question, level reading comprehension question, English textbook